ANALISIS PERBANDINGAN METODE MENGHAFAL Al-QUR’AN PADA SANTRI PUTRI (Studi Pesantren Darussalam Dan Pesantren Harsallakum Kota Bengkulu) - Apriani, Ria; Khoiri, Qolbi; Delta Fitrianah, Rossi (JPT : Jurnal Pendidikan Tematik, 2020)
The main problem of this research is how the method of students in memorizing the Qur'an. By looking at the condition of female students not only memorizing the Qur'an in the dormitory, they also have to memorize subjects at school. The research entitled "Comparative Analysis of Al-Qur'an Memorizing Methods for Female Santri (Study of Darussalam Islamic Boarding School and Harsallakum Islamic Boarding School Bengkulu City)" has a problem formulation, How is the process of implementing memorizing the Qur'an in female students how to analyze the method of memorizing the Qur'an 'an for female students of Darussalam Islamic Boarding School and Harsallakum Islamic Boarding School. The type of research used is descriptive qualitative research to describe systematically the facts found in the field based on observations and interviews and other documents. The object of this research is asatidz and the santriwatai in the two Islamic boarding schools, and the data collection procedures used are structured interviews, and documentation. Data analysis is carried out by examining existing data, then conducting data reduction, data presentation, drawing conclusions and holding the end of this data analysis is to hold data validity by using triangulation observation persistence. Based on the results of research and discussion showing the similarities and differences in the methods used in memorizing the Qur'an in the two Islamic boarding schools, it shows that the students can memorize the Qur'an in accordance with the law of reading, using a predetermined method that aims to facilitate students in memorizing the Qur'an. The methods used in the Darussalam Islamic boarding school are the bin-nazhar method and the tahfizh method, while the Harsallakum Islamic boarding school uses the talqin and tikrar methods, and the tahfizh method by using the Al-Qur'an memorization method so that the students can memorize the Al-Qur'an which want to be memorized correctly without any errors in makharijul letters, harakat and so on. And it is hoped that the students will be more focused and concentrated in memorizing the Qur'an with good reading and understanding, so that the target can be achieved. and from friends.